Kinetic responses of running shoes submitted to prolonged use: a case report - Roberto Bianco; Fernanda Michelone Acquesta; Ana Paula da Silva Azevedo; Carina Helena Wasem Fraga; Sandro Barone; Luiz Mochizuki; Alberto Carlos Amadio; Júlio Cerca Serrão (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2013)
The purpose of this study was to analyze the kinetic responses of running shoes submitted to prolonged use. Four shoes (R1, R2, T1 and T2) were used for 500 km except for T1 which was used for 1000 km. At every 100 km, Ground Reaction Force (GRF) and plantar pressure measurements were collected. In T2, there was a slight trend of increase in Loading Rate of the first peak of GRF with increasing distance. R1, R2 and T1 showed no trend of increase in Loading Rate values. Shoe T1 showed a slight tendency of increase in Loading Rate values when the distance was considered up to 1000 km. All running shoes showed a high variability in peak pressure values, but no trend of increase was observed. On the contrary, T1, T2 and R2 showed a trend of decrease in peak pressure values with increasing use. Therefore, there is no consistent evidence or trend of increase in Loading Rate and Peak Pressure values that would suggest worsening in external load attenuation.